Total Physical Response Method as a Stress-Free Learning Method in English Language Teaching: English - Veren; Yohanes Gatot Sutapa Yulia; Regina (Prodi Tadris Bahasa Inggris, 2023)
This study investigates how teaching young students English using Total Physical Response can be a stress-free method. It highlights that learning English can be stressful for some students, particularly young students like kindergarteners who have different comprehension levels than adults. Therefore, the teaching process must be engaging and the environment appropriate for young minds. TPR, which requires coordination of speaking and movement, has been identified as a highly effective strategy for teaching young children. This approach has been widely used in kindergartens and elementary schools, making learning enjoyable and aiding in retaining English words and expressions. Studies have shown TPR to be effective for young students and students in junior high, senior high, and adulthood. TPR has also been found suitable for dyslexic and visually impaired students, offering benefits such as stress reduction, improved comprehension, and memory enhancement. However, TPR has limitations, including the necessity for teachers to adhere to the curriculum, potentially causing stress and limiting student creativity, as activities focus on mimicking the teacher rather than generating original sentences.